Risk factors for persistent tomographic abnormalities at 6 months of follow-up in a cohort of hospitalized patients with moderate and severe COVID-19 living at high altitude - Rincon-Alvarez, Emily; Gonzalez-Garcia, Mauricio; Ali-Munive, Abraham; Casas, Alejandro; Proaños, Nadia Juliana; Giraldo-Cadavid, Luis Fernando; Moreno, Angelica; Pérez, Carolina; Rubiano, Wendy; Cogollo, Mary; Parada-Tovar, Patricia; Torres-Duque, Carlos A. (Frontiers in Medicine, 2023)
Introduction After COVID-19, functional and tomographic lung alterations may occur, but there are no studies at high altitude where, due to lower barometric pressure, there are lower levels of arterial oxygen pressure and saturation in both normal subjects and patients with respiratory disease. In this study, we evaluated the computed tomographic (CT), clinical, and functional involvement at 3 and 6 months post-hospitalization in survivors with moderate-severe COVID-19, as well the risk factors associated with abnormal lung computed tomography (ALCT) at 6 months of follow-up. Materials and methods Prospective cohort, after hospitalization for COVID-19, of patients older than 18 years residing at high altitude. Follow-up at 3 and 6 months with lung CT, spirometry, diffusing capacity of the lung for carbon monoxide (DLCO), six-minute walk test (6MWT), and oxygen saturation (SpO2). Comparisons between ALCT and normal lung computed tomography (NLCT) groups with X2 and Mann–Whitney U test, and paired test for changes between 3 and 6 months. A multivariate analysis was performed to evaluate the variables associated with ALCT at 6-month follow-up. Results We included 158 patients, 22.2% hospitalized in intensive care unit (ICU), 92.4% with typical COVID CT scan (peripheral, bilateral, or multifocal ground glass, with or without consolidation or findings of organizing pneumonia), and median hospitalization of 7 days. At 6 months, 53 patients (33.5%) had ALCT. There were no differences between ALCT and NLCT groups in symptoms or comorbidities on admission. ALCT patients were older and more frequently men, smokers and hospitalized in ICU. At 3 months, ALCT patients had more frequently a reduced forced vital capacity (< 80%), and lower meters walked (6MWT) and SpO2. At 6 months, all patients improved lung function with no differences between groups, but there were more dyspnea and lower exercise SpO2 in ALCT group. The variables associated with ALCT at 6 months were age, sex, ICU stay, and typical CT scan. Conclusion At 6-month follow-up, 33.5% of patients with moderate and severe COVID had ALCT. These patients had more dyspnea and lower SpO2 in exercise. Regardless of the persistence of tomographic abnormalities, lung function and 6MWT improved. We identified the variables associated with ALCT.